Psychological Status of Healthcare Professionals of Bangladesh during the COVID-19 Pandemic - Ali, Md Mahbub; Naharin, Noor E; Hossain, SM Eqbal; Manjur, Mushfique (Journal of Monno Medical College, 2023)
Background: The wellbeing of Healthcare professionals (HPs) across the world had been severely affected by the COVID-19 pandemic. Previous researches on other similar infectious diseases consistently showed that many HPs reported symptoms of anxiety and depression, both during and after the outbreak, causing a severe impact on their coping abilities, in some cases with long-lasting effects. Objectives: The present study was designed to find out the impact on mental health of the HPs in Bangladesh during COVID-19 pandemic. Methodology: This survey-based cross-sectional study was carried out in Combined Military Hospital, Bogura, a tertiary hospital in Bangladesh. The study was conducted during 15-20 August, 2020, including 303 HPs during the COVID-19 pandemic. The study incorporated the patient health questionnaire (PHQ-2) and generalized health questionnaire (GAD-2), validated for screening of Major Depressive Disorder (MDD) and Generalized Anxiety Disorder (GAD) respectively. Results: Among the respondents, majority were males (201, 66.34%), between 20-29 years of age (127, 41.92%), married (244, 80.53%), fertile (205, 67.66%) and health assistants (151, 49.83%). Some 137(45.21%) respondents were involved directly to treat diagnosed cases of COVID-19 and 20(06.60%) had been suffering from insomnia. A total of 73(24.09%) HPs remained in anxiety every time that their family members may be affected by COVID-19 through them. The MDD was found in 77(25.41%) respondents and GAD in 42(13.86%). The MDD was found more (25.40% versus 23.53%) in the HPs who were staying without family, but GAD (21.57% versus 12.30%) and Anxiety to infect family members through them was remarkably higher (49.10% versus 19.05%) in the HPs who stayed with family. Conclusion: The present survey showed that a remarkable number of HPs experienced anxiety and depression due to prevailing COVID-19 pandemic Journal of Monno Medical College, June 2023; 9 (1): 15-19